2022
DOI: 10.1111/jocn.16348
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity and specificity of proposed Richards‐Campbell Sleep Questionnaire cut‐off scores for good quality sleep during an ICU stay

Abstract: Background: The 5-visual analogue scale Richards-Campbell Sleep Questionnaire subjective sleep measure is widely used in intensive care. A cut-off score indicative of good quality sleep has not been established and is required to guide the categorisation of individual patient and unit wide sleep quality. Design and Methods: The aim was to determine the global Richards-Campbell Sleep Questionnaire cut-off score for good to very good sleep during an intensive care unit stay in non-ventilated patients. The study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Cut-off scores for healthy sleep (population norms) have not yet been established, but there is beginning evidence that a score of 63 mm is a reliable cut-off score for good-quality sleep. 16 Darby et al 9 reported a prospective quality improvement study in which data were collected for delirium-free days After the implementation of a not dissimilar study by Patel et al 10 patients reported an increase in sleep quality (pre: 60.8 ± 3.5 vs. post: 75.9 ± 2.24 mm) and the incidence of delirium was lower (pre: 33 % [n = 55/167] vs. post: 14 % [n = 24/171]). In this study the difference between nocturnal mean light and sound levels and compliance measured before and after the implementation of the intervention indicated that clinicians adopted many components (sound pre: 68.8 ± 4.2 dB vs. post: 61.8 ± 9.1 dB; light levels per: 594 ± 88.2 lux vs. post: 301 ± 53.5 lux).…”
Section: Review Of the Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…Cut-off scores for healthy sleep (population norms) have not yet been established, but there is beginning evidence that a score of 63 mm is a reliable cut-off score for good-quality sleep. 16 Darby et al 9 reported a prospective quality improvement study in which data were collected for delirium-free days After the implementation of a not dissimilar study by Patel et al 10 patients reported an increase in sleep quality (pre: 60.8 ± 3.5 vs. post: 75.9 ± 2.24 mm) and the incidence of delirium was lower (pre: 33 % [n = 55/167] vs. post: 14 % [n = 24/171]). In this study the difference between nocturnal mean light and sound levels and compliance measured before and after the implementation of the intervention indicated that clinicians adopted many components (sound pre: 68.8 ± 4.2 dB vs. post: 61.8 ± 9.1 dB; light levels per: 594 ± 88.2 lux vs. post: 301 ± 53.5 lux).…”
Section: Review Of the Evidencementioning
confidence: 99%
“…Global sleep quality is the average of the VAS scores. Cut‐off scores for healthy sleep (population norms) have not yet been established, but there is beginning evidence that a score of 63 mm is a reliable cut‐off score for good‐quality sleep 16 …”
Section: Review Of the Evidencementioning
confidence: 99%
“…The RCSQ was specifically designed for use in the ICU population and uses five visual analogue scales to assess the domains of sleep latency, sleep efficiency, sleep depth, number of awakenings and overall sleep quality (Figure 1 )[ 141 ]. Individual domain scores can be interpreted respectively or combined into a global score, with a score of ≥ 63 out of 100 reported as the optimal cut-off for self-reported ‘good sleep’[ 142 ]. Both content and criterion validity have been established against polysomnography[ 143 ].…”
Section: Subjective Measurement Of Sleep In the Critically Illmentioning
confidence: 99%